The Influence of Policy Transparency, Public Participation, Bureaucratic Responsiveness, Service Quality, and Public Trust on Perceived Effectiveness of Local Economic Policy - May Vitha Rahmadhani; Fitri Melawati; Irfansyah; Aryo Prakoso (PT. Maju Malaqbi Makkarana, 2026)
The effectiveness of local economic policy is essential for promoting sustainable regional development and improving community welfare. However, citizens' perceptions of policy effectiveness are influenced not only by policy outcomes but also by the quality of governance practices implemented by local governments. This study aimed to examine the influence of policy transparency, public participation, bureaucratic responsiveness, service quality, and public trust on the perceived effectiveness of local economic policy. A quantitative research approach with an explanatory research design was employed. Primary data were collected through a structured questionnaire distributed to 200 respondents selected using purposive sampling. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS), including descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression analysis, the coefficient of determination (R²), t-tests, and F-tests. The results revealed that all measurement instruments were valid and reliable, and the data satisfied the assumptions required for multiple linear regression analysis. The findings indicated that policy transparency, public participation, bureaucratic responsiveness, service quality, and public trust each have a positive and significant influence on the perceived effectiveness of local economic policy. Furthermore, the F-test demonstrated that all independent variables simultaneously have a significant effect on the dependent variable. Among the five predictors, public trust was identified as the strongest determinant of perceived policy effectiveness. The study concludes that strengthening good governance practices through transparency, citizen participation, responsive bureaucracy, high-quality public services, and institutional trust can substantially improve public perceptions of local economic policy effectiveness. These findings provide practical implications for local governments in designing and implementing more effective, accountable, and citizen-oriented economic policies